ABOUT OF INSPECTION OF INSURANCE COMPANIES’ FINANCIAL REPORTINGS BY AUDIT ORGANIZATIONS - Xayitboev Muxammadi Israpilovich; Abduraimova Maftunaxon Ahmatovna; Ovlaev Suhrob Temur o’g’li; Yo’lchiev Oybek Ulug’bek o’g’li (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2025)
This article examines the procedures for auditing the financial statements of insurance companies, the requirements and rules of the audit of financial statements, as well as the procedure for formalizing audit conclusion and reports.